Exploring Taxation Understanding among Individual Taxpayers at Sekolah Pelayaran Bhakti Samudera - Sahrul Anam; Firman Eka Putra; Acynthia Ayu Wilasittha; Tantina Haryati; Sofie Yunida Putri (Nusantara Science and Technology Proceedings, 2023)
This community engagement initiative aims to assess the extent of the understanding among the academic community of Sekolah Pelayaran Bhakti Samudera regarding the reporting of Article 21 personal income tax (PPh 21). The level of understanding was gauged through the distribution of a questionnaire, which included inquiries about the registration of taxpayers within the Sekolah Pelayaran Bhakti Samudera environment and participants' comprehension of taxation and their tax obligations. The taxpayer registration process will assist the community engagement team in developing materials for socialization and assistance in filing individual income tax returns (SPT PPh Orang Pribadi) to be conducted in the future. Based on the questionnaire, data were obtained from 26 participants, with 61.5% of them having a Taxpayer Identification Number (NPWP), while the rest did not possess an NPWP. This aligns with the condition of the academic community in the school, which typically earns income below the Non-Taxable Income Threshold (PTKP). Regarding the understanding of tax reporting, the academic community at Sekolah Pelayaran Bhakti Samudera still lacks a solid grasp of the subject. A total of 20 respondents out of 26 participants exhibited a low level of understanding of tax reporting. Consequently, many members of the academic community remain unfamiliar with the tax reporting obligations of individual taxpayers with NPWP. This situation is further supported by the school's practice of not providing PPh 21 withholding tax slip due to the academic community's income falling below the PTKP threshold.